Breast Feeding Practices Among Rural Women - Samreen Naqvi; Taj Mohammad (International Journal of Women's Health Nursing And Practices, 2023)
Introduction: Breastfeeding is an unequalled way of providing ideal food for the healthy growth and development of infants. As per the national family health survey-3 (NFHS-3), only 46% of the Indian infants between 0 and 6 months are exclusively breastfed. Hence the following study was done to know the practice of breastfeeding in mothers of rural and urban areas of India. Method- The study was carried out in a rural region and managed by the Community Medicine Department at the Phc Aghwanpur in Moradabad. A predesigned, pretested semi-structured "questionnaire" was used to interview mothers. During that time, 361 mothers in all were interviewed. Software called SPSS was used for the statistical analysis. Result: The majority of the mothers who gave birth at the health facility, where mothers are encouraged by health personnel to breastfeed immediately after delivery, may be the cause of the high rates observed in our current study.19.1% of the children in the current study got prelacteal feed, which included some ghutti (33.3%) and honey (46.3%). artificial milk before the first breast milk (15.9%). Conclusions: Strong predictors of breastfeeding behaviours were maternal age, the mother's work, the size of the household, and the neighbourhood in which she lived. It is strongly advised that the study region maintain access to information on proper breastfeeding techniques and promote breastfeeding, particularly among young women.
Keywords: Breastfeeding; healthy growth; infants; mothers; women